Medical Staff Social Practice and Attitude towards People with Mental Disorders - Oksana, Stadnik; Bohdan, Sliushchinskiy; Nataliia, Varha; Olena, Khodus; Nataliia, Polovaia (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Considering the social vulnerability of the people with mental disorders and a certain dualism of treatment practice within this social category of people and beginning from socializing process to isolation in Ukrainian society, it becomes relevant to prevent the formation of antisocial and stigmatizing consequences toward the patients with mental disorders in society. Objective: The article's aim involves the social practice of studying and attitude toward patients with mental disorders. They are based on the results of sociological questionnaires. Methods: The questionnaire is based on psychiatrists and psychiatric hospitals’ medical staff surveys. It covers 505 medical workers of the Regional Clinical Psychiatric Hospital in the Zaporizskiy region of Ukraine. Results: The result points to the domination of neutral attitude toward the mentally disabled people among the respondents-experts (medical and junior medical staff including), which in turn causes several negative consequences as follows: lack of understanding of treatment differences concerning the mentally healthy and mentally ill; a latent reluctance for changing the social treatment practice towards the mentally ill in a more humane way; distancing from the mentally ill; a change of verbally-behavioral practice to antisocial, hostile ones. etc. Conclusions: Despite the globalization of the modern world, the local composition of verbal-behavioral social practice toward people with mental disorders is influenced by socio-cultural, economic, and political determinants.